(untitled) (Encuentros, 2019)
This paper shows the result of the validation of a set of professional skills evaluated from important and applicability levels by publicist in Bogota. For that, 19 professional competencies were identified, extracted from theoretical references and from the analysis of the professional profiles and skills of advertising programs accredited in Colombia. The methodology was developed under a mixed approach, of descriptive type, with participation of publishers in Bogota. Data collection was done by means of the survey technique, while data analysis was based on descriptive statistics. The results obtained make it possible to expose the changes in the advertising exercise and the importance of the constant updating of knowledge by the professionals in order to maintain and advance in the work environment Keyword: publicist profile; specific skills of publicist; publicists, professional in advertising, professional skills, advertising.